PHENOMENOLOGY OF KYRGYZ ETHNIC CONSCIOUSNESS: MUSICAL THINKING (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The musical layer of culture is the most ancient, conservative, and difficult or completely resistant identity to foreign cultural influence and impact. That is, musical thinking should be considered as a product and as a process of (self) identification. The unconscious is the invisible denominator of musical thinking. The individual constructs the perception of musical works from associations and analogies of his experience, while insight can be considered as the comprehension of the meaning of the entire musical work. The meditative nature of k’yu instrumental pieces leads listeners to a fusion with symbolic value, being conductors of the social, and therefore ethnic.
Keywords: Kyrgyz traditional music, semantics, k’yu, komuz, artistic reflection, cognition, musical thinking, identity.